Central and peripheral choroidal thickness and eye length changes during accommodation. (4th January 2023) - Kaphle, Dinesh; Schmid, Katrina L.; Suheimat, Marwan; Read, Scott A.; Atchison, David A.
Abstract: Purpose: Eye length increases during accommodation, both on‐axis and in the periphery. The aim of this study was to determine whether the peripheral choroid thins with accommodation and to determine the relationship with eye length changes measured at the same location. Methods: Subjects included 53 young adults in good ocular and general health, with 19 emmetropes and 34 myopes. Measurements from the right eye were made for 0 D and 6 D accommodation stimuli for ±30° horizontal visual field/retinal locations in 10° steps. Valid eye length and choroidal thickness measurements were obtained for 37 and 47 participants, respectively, and both measures were taken for 31 participants. 2.5% phenylephrine was instilled to dilate the pupils. Participants turned their eyes, without head movement, to fixate targets and to make the target 'as clear as possible' during measurements. Correction was made for the influence of lens thickness changing at different peripheral angles. Choroidal thickness was measured with a spectral‐domain‐Optical Coherence Tomographer. For peripheral images, the internal cross target on the capture screen was moved from the centre to 17.25° nasal/temporal positions. Results: In accordance with previous literature, eye length increased with accommodation. The greatest change (mean ± SD) of 41 ± 17 μm occurred at the centre, with a mean change across the locations of 33 μm. There were no significant differences between emmetropes and myopes. Choroidal thickness decreased with accommodation, with changes being about two‐thirds of those occurring for eye length. The greatest change of −30 ± 1 μm occurred at the centre, with a mean change of −21 μm. Greater choroidal thinning occurred for myopes than for emmetropes (23 ± 11 vs. 17 ± 8 μm, p = 0.02). Conclusions: With accommodation, eye length increased and the choroid thinned, at both central and peripheral positions. Choroidal thinning accounted for approximately 60% of the eye length increase across the horizontal ±30°.